Outcome predictors in COVID-19: An analysis of emergent systemic inflammation indices in Mexican population - Gutiérrez-Pérez, Ilse Adriana; Buendía-Roldán, Ivette; Pérez-Rubio, Gloria; Chávez-Galán, Leslie; Hernández-Zenteno, Rafael de Jesus; Aguilar-Duran, Hiram; Fricke-Galindo, Ingrid; Zaragoza-García, Oscar; Falfán-Valencia, Ramcés; Guzmán-Guzmán, Iris Paola (Frontiers in Medicine, 2022)
Introduction: The systemic viral disease caused by the SARS-CoV2 virus called coronavirus disease 2019 (COVID-19) continues to be a public health problem worldwide. Objective: This study is aimed to evaluate the association and predictive value of indices of systemic inflammation with severity and non-survival of COVID-19 in Mexican patients. Materials and Methods: A retrospective study was carried out on 807 subjects with a confirmed diagnosis of COVID-19. Clinical characteristics, acute respiratory distress syndrome (ARDS), severity according to PaO2/FiO2 ratio, invasive mechanic ventilation (IMV), and non-survival outcome were considered to assess the predictive value and the association of eleven systemic inflammatory indices derived from hematological parameters analyzed at the hospital admission of patients. The receiver operating characteristics curve was applied to determine the thresholds for eleven biomarkers, and their prognostic values were assessed via the Kaplan-Meier method. Results: 26% of the studied subjects showed COVID-19 severe (PaO2/FiO2 ratio <100), 82.4% required IMV, and 39.2% were non-survival. The indices NHL, NLR, RDW, and SIRI displayed predictive values for COVID-19 severe and non-survival. NHL, SIRI, and NLR showed predictive value for IMV. The cut-off values for RDW (OR = 1.85, p <0.001), NHL (OR = 1.67, p = 0.004) and NLR (OR = 1.56, p = 0.012) were mainly associated with severe COVID-19. NHL (OR = 3.07, p <0.001), AISI (OR = 2.64, p <0.001) and SIRI (OR = 2.51, p <0.001) were associated with IMV support, while for non-survival the main indices associated were NHL (OR = 2.65, p <0.001), NLR (OR = 2.26, p <0.001), SIRI (OR = 1.67, p = 0.002) and SII (OR = 1.50, p = 0.010). The patients with an RDW, PLR, NLR, MLR, SII and NHL above the cut-off had a survival probability of COVID-19 50% lower, with an estimated mean survival time of 40 days. Conclusion: The emergent systemic inflammation indices NHL, NLR, RDW, SII, and SIRI have a predictive power of COVID-19 severe, IMV support, and low survival probability during hospitalization by COVID-19 in Mexican patients.